Association between pre-diagnostic dietary copper, zinc, and copper-to-zinc ratio and severity of ovarian cancer - Yin, Jia-Li; Tao, Tao; Wen, Zhao-Yan; Wang, Ran; Sun, Ming-Hui; Gao, Chang; Chang, Yu-Jiao; Yan, Shi; Qin, Xue; Zhao, Yu-Hong; Wang, Lan; Gao, Song (Frontiers in Nutrition, 2022)
Abstract Background: The impact of dietary trace elements intake on ovarian cancer (OC) severity is unknown. Objective: We firstly explore the relationship between dietary copper (Cu), zinc (Zn), and copper-to-zinc (Cu/Zn) ratio and severity of OC. Methods: This cross-sectional study included 701 women from the ovarian cancer follow-up study between 2015 and 2020. Dietary information was collected by a validated food frequency questionnaire. The severity information of OC including age at diagnosis, histological type, International Federation of Gynecology and Obstetrics stage, and histopathologic grade was ascertained from medical records. Logistic regression model was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) of aforementioned associations. Results: Among 701 participants, the number of patients age at diagnosis older than 50 were 443 (63.2%). The number of patients diagnosed as serous, III–IV stage, and poorly differentiation OC were 477 (68.05%), 336 (47.93%) and 597 (85.16%) respectively. In addition, compared with the lowest tertile intake, higher possibility of non-serous OC was associated with the pre-diagnosis dietary Cu (OR = 2.39, 95% CI = 1.28-4.47, p trend < 0.05) and Cu/Zn ratio (OR = 2.06, 95% CI = 1.26-3.39, P trend < 0.05) in the highest tertile intake. The risk of poorly differentiation OC at diagnosis was significant inversely related to dietary Cu intake (OR = 0.40, 95% CI = 0.18-0.88, P trend < 0.05). Besides, the results of subgroup analyses were consistent with the main findings but not all of them showed statistical significance. Conclusion: Pre-diagnostic dietary Cu and Cu/Zn ratio were contributed to reducing the severity of OC at diagnosis, especially for the risk of serous OC and poorly differentiation OC.